2013
DOI: 10.1097/wnr.0b013e32835edbfa
|View full text |Cite
|
Sign up to set email alerts
|

Tickling increases dopamine release in the nucleus accumbens and 50 kHz ultrasonic vocalizations in adolescent rats

Abstract: Adolescent rats emit 50 kHz ultrasonic vocalizations, a marker of positive emotion, during rough-and-tumble play or on tickling stimulation. The emission of 50 kHz ultrasonic vocalizations in response to tickling is suggested to be mediated by dopamine release in the nucleus accumbens; however, there is no direct evidence supporting this hypothesis. The present study aimed to elucidate whether play behavior (tickling) in adolescent rats can trigger dopamine release in the nucleus accumbens with hedonic 50 kHz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…As both playing with a conspecific (Trezza et al, 2010) as well as producing and hearing 50-kHz calls (Brudzynski, 2007;Sadananda et al, 2008) enhances activity in reward-related brain areas, it is possible that the increased opportunity for physical contact afforded by the devocalized rat compensates for, or even exceeds, the reward of interacting with intact partners. Indeed, several studies have shown that rats find tickling by a human hand to be highly rewarding, prompting them to emit high frequencies of 50-kHz calls (Hori et al, 2013;Panksepp, 2007;Panksepp and Burgdorf, 2000), further supporting the idea that physical contact is rewarding. Thus, the changed defense by the devocalized partner and the increase in emission of calling by the intact partner, leads to levels of play in pairs of rats containing an intact and a devocalized rat that are higher than in pairs of intact rats (present study) and in pairs of devocalized rats (Kisko et al, 2015).…”
Section: Discussionmentioning
confidence: 83%
“…As both playing with a conspecific (Trezza et al, 2010) as well as producing and hearing 50-kHz calls (Brudzynski, 2007;Sadananda et al, 2008) enhances activity in reward-related brain areas, it is possible that the increased opportunity for physical contact afforded by the devocalized rat compensates for, or even exceeds, the reward of interacting with intact partners. Indeed, several studies have shown that rats find tickling by a human hand to be highly rewarding, prompting them to emit high frequencies of 50-kHz calls (Hori et al, 2013;Panksepp, 2007;Panksepp and Burgdorf, 2000), further supporting the idea that physical contact is rewarding. Thus, the changed defense by the devocalized partner and the increase in emission of calling by the intact partner, leads to levels of play in pairs of rats containing an intact and a devocalized rat that are higher than in pairs of intact rats (present study) and in pairs of devocalized rats (Kisko et al, 2015).…”
Section: Discussionmentioning
confidence: 83%
“…Among these, 50% (n = 2) found at least some positive effects and 50% (n = 2) found no effects. Tickling increased dopamine release in the nucleus accumbuens [28] and decreased adrenaline and noadrenaline after fear conditioning [22]. However, tickling was never found to effect corticosterone in the feces [23, 25] or blood [22].…”
Section: Resultsmentioning
confidence: 99%
“…One article attempted to use tickling combined with the application of the psychotomimetic drug phencyclidine to model the negative symptoms of schizophrenia, but concluded that it was unclear if this model would be valid or not [53]. Another article successfully concluded that 50-kHz calls in response to tickling were mediated by dopamine release as evidenced by a decrease in calls after application of dopamine agonists [28]. This article was using tickling to model the importance of play behavior during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…There is also overlap with the first four core emotions. Hori, Shimojo, and Tokunaga, et al (2013) found that tickling rats and play triggered dopamine release in the nucleus accumbens. This finding would overlap with the seek emotional system.…”
Section: Lust Nurture and Playmentioning
confidence: 99%